PENDIDIKAN AKHLAK MENURUT IMAM HASAN AL-BANNA DALAM KITAB MAJMUATU RASA’IL - choli, Ifham; Farhana (Pascasarjana Universitas Islam Jakarta, 2022)
important issue, so that every aspect of the Islamic education process always fosters noble character. Morals are traits that have been embedded in the soul that encourage one's behavior easily so that it becomes habitual behavior. This study uses the type of research in the form of Library Research (Library Research). Library research is a research conducted by reading, studying books by quoting from various theories and opinions that have a relationship with the problem under study. This study takes the thinking of Imam Hasan Al-Banna because Imam Hasan has a character of its own renewal that distinguishes it from the previous scholars. Among the most important aspects of education in the Ta'lim Treatise is the moral aspect. Among the most important aspects of education in the Ta'lim Treatise is the moral aspect. Hasan al Banna called it the